Design of non-equal-strut stent hoops for structural optimization of thoracic aortic stent-grafts. Issue 1 (3rd January 2022) - Yan, Shiju; Song, Chengli; Si, Yi; Zhao, Yiwen
Abstract: Background: Endovascular aortic aneurysm repair (EVAR) with stent-grafts is used widely for the treatment of thoracic aortic aneurysms (TAA). Inappropriate design of stent-grafts may lead to complications such as endoleak, stent-graft migration and new entries, causes of which may be inappropriate radial support force or insufficient longitudinal flexibility of the stent-grafts. Material and methods: To improve the mechanical performance of the stent-grafts, a type of non-equal-strut stent hoops was proposed, and the influence of structural parameters on the mechanical performance was studied. Results: Results of numerical simulation and physical experiments show that by using the proposed non-equal-strut stent hoops, radial support force and longitudinal flexibility of stent-grafts can be reconciled and balanced. Conclusion: Results of this study could be used to facilitate radial force control and longitudinal flexibility enhancement in the design of aortic stent-grafts.